ECONOMIC FEASIBILITY ANALYSES OF COAL- BASED ACTIVATED CARBON PLANT IN INDONESIA - Gandhi Kurnia Hudaya; Fahmi Sulistyohadi; Ika Monika (Puslitbang tekMIRA, 2014)
Technology to make activated carbon from coal has been developed from laboratory to pilot plant scales with capacity of 1 ton/day. The results of previous experiments showed that the quality of coal activated carbon has complied with the standard of quality activated carbon from coconut shell (SNI). In addition, the result of coal utilization process showed that activated carbon can be used for water purification on hatchery, and waste water treatment in textiles and rubber industries. Although the technology and the quality have been reached, but for the production it still needs economic feasibility analysis. Economic feasibility analysis is necessary for coal- based activated carbon plant at commercial scale by giving an indication about economic value of the project. The indicators used in the analysis are Net Present Value (NPV), Return on Investment (ROI), Internal Rate of Return (IRR) and Payback Period. Calculation of financial indicators for the activated carbon project produced Rp 49.17 billion NPV, 50% ROI, 68,25% IRR and 1 year 4 months Payback Period. Based on that calculation, it can be concluded that the coal-based activated carbon plant would be economically feasible under certain operational scenarios. This study is expected to become an economic reference material and can attract inves- tors to construct the commercial plant.